Edwin is twice as old as ruel. in 3 years, edwin willbe 13 years lessthan thrice as old as ruel. Find thier ages

Edwin is 14. Ruel is 7.

In 3 years Edwin will be 17. Edwin will be 10. (3*10 - 13 = 17)

Let x=Ruel's age now, and 2x=Edwin's age now.

2x+3=3(x+3)-13

2x+3=3x+9-13

2x+3=3x-4

2x+7=3x

7=x

If you are going to post these, the least you could do is rate them as Fixya. :-) Thanks!

Posted on Dec 12, 2008

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

Let Adjoa's age be x and Kwame's y.

- Adjoa is 3 years older than Kwame: x=y+3
- Seven years ago sum of their ages was 13: (x-7)+(y-7)=13
- Now you substitute first equation into second equation: (y+3-7)+(y-7)=13
- 2y-4-7=13
- 2y=24
- y=24/2=12 years
- x=y+3=12+3=15 years
- sum of their present ages is x+y=12+15=27 years

Sep 27, 2011 | Office Equipment & Supplies

Let m be Marian's age, d Diana's age and c Carlos age.

I hope I helped :)

- sum of ages is 17: m+d+c=17
- two years from now Marian will be twice as old as Diana: m+2=2*(d+2) so m+2=2d+4 so 2d=m-2 or d=(m-2)/2=m/2-1
- Carlos will be half as old as Marian 4 years from now: c+4=1/2(m+4) or c+4=m/2+2 or c=m/2-2
- now: m+d+c=m+m/2-1+m/2-2=17
- 2m=17+3=20
- m=20/2=10 years
- d=m/2-1=5-1=4 years
- c=m/2-2=5-2=3 years

I hope I helped :)

Sep 18, 2011 | Office Equipment & Supplies

Todd is 4 years old.

Let Tom's age = X

Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )

X+13 = 3Y + 21

X = 3Y + 8

So if:

X=5Y

and

X=3Y+8

Then:

5Y=3Y+8

2Y=8

Y=4

I hope that helps.

Joe.

Let Tom's age = X

Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )

X+13 = 3Y + 21

X = 3Y + 8

So if:

X=5Y

and

X=3Y+8

Then:

5Y=3Y+8

2Y=8

Y=4

I hope that helps.

Joe.

Sep 14, 2011 | Office Equipment & Supplies

Correction: **Bob is thrice as old as Peter.**

Let b be the current age of Bob, and p the current age of Peter.**Now, b=3p**

Six years earlier the relations was:**b-6=4*(p-6)=4p-24.**

Take the 6 to the right side leaving b=4p-18

Remember that now b=3p. Use it in the equation above

b=(3p)=4p-18, This becomes 3p=4p-18 or 0=p-18, and**p=18**

**Peter is 18 years old, and Bob is 3*18=54 years old.**

Verification: 6 years ago Peter was 12 years old and Bob 48 years old. 48/12=4.

Let b be the current age of Bob, and p the current age of Peter.

Six years earlier the relations was:

Take the 6 to the right side leaving b=4p-18

Remember that now b=3p. Use it in the equation above

b=(3p)=4p-18, This becomes 3p=4p-18 or 0=p-18, and

Verification: 6 years ago Peter was 12 years old and Bob 48 years old. 48/12=4.

Aug 10, 2011 | Texas Instruments TI-84 Plus Calculator

Let the brother's age be x:

16years for Mary = 4x years for Brother

From equation: 4x = 16

x = 4

Therefore, the brother is 4 years old.

__Mary__ __ Brother__

16 4

After 4 years +__4 4__

20 8

After the next 4 years +__4 4__

24 12

24 is twice as old as 12; therefore for the sister to be twice as old as brother she will 24years when her brother is 12 years.

Or by calculation;

If 4 is the age for the brother, when the sister is 16, and y years will pass for the to be such that the sister is twice as old as the brother, then;

16 + y = 2(4 + y)

16 + y = 8 + 2y

16 - 8 = 2y - y

8 = y

Therefore, 8 years elapse before the sister is twice as old as the brother.

Sister will be: (16 + 8) = 24years

Brother will be: (4 + 8) = 12years

16years for Mary = 4x years for Brother

From equation: 4x = 16

x = 4

Therefore, the brother is 4 years old.

16 4

After 4 years +

20 8

After the next 4 years +

24 12

24 is twice as old as 12; therefore for the sister to be twice as old as brother she will 24years when her brother is 12 years.

Or by calculation;

If 4 is the age for the brother, when the sister is 16, and y years will pass for the to be such that the sister is twice as old as the brother, then;

16 + y = 2(4 + y)

16 + y = 8 + 2y

16 - 8 = 2y - y

8 = y

Therefore, 8 years elapse before the sister is twice as old as the brother.

Sister will be: (16 + 8) = 24years

Brother will be: (4 + 8) = 12years

Aug 02, 2011 | Computers & Internet

So the father is 3 times as old as his daughter.

Let F represent the age of the fatherLet D represet the age of the daughter

So we know from the first sentence,

F = 3 * D

From the second sentence, 12 years from now the father is 1 year les than twice his daughters age,

First, lets assume it's not 12 years from now (to avoid confusion), we would haveF + 1= 2 * D

But since its 12 years from now, we have to add 12 to both ages

(F + 12) + 1 = 2 * (D + 12)

Let's simplify a bit,

F + 13 = 2 * D + 24F = 2D + 11

Now we have to solve these two equations together, we can plug the first equation into the second,

F = 3 * DF = 2 * D + 11

3 * D = 2 * D + 11D = 11

So the daughter is 11 years old, we can find out how old the father is by plugging into the first equation

F = 3 * DF = 3 * 11F = 33

So the father is 33 and the daughter is 11.

Let F represent the age of the fatherLet D represet the age of the daughter

So we know from the first sentence,

F = 3 * D

From the second sentence, 12 years from now the father is 1 year les than twice his daughters age,

First, lets assume it's not 12 years from now (to avoid confusion), we would haveF + 1= 2 * D

But since its 12 years from now, we have to add 12 to both ages

(F + 12) + 1 = 2 * (D + 12)

Let's simplify a bit,

F + 13 = 2 * D + 24F = 2D + 11

Now we have to solve these two equations together, we can plug the first equation into the second,

F = 3 * DF = 2 * D + 11

3 * D = 2 * D + 11D = 11

So the daughter is 11 years old, we can find out how old the father is by plugging into the first equation

F = 3 * DF = 3 * 11F = 33

So the father is 33 and the daughter is 11.

Jul 19, 2011 | Computers & Internet

Within 11 years, the age of Peter will be half the square of the age he was 13 years ago. Calculate the current age of Peter.

Suzy is ten years older than Billy, and next year she will be twice as old as Billy. How old are they now?

Suzy is ten years older than Billy, and next year she will be twice as old as Billy. How old are they now?

Sep 22, 2010 | Computers & Internet

Hi,

Let the present age of the Rodney = X

present Age of the Jasmin = Y

As per the Situation,

Y-9 = 2 (X - 9)

Y-9 = 2X - 18

Y = 2X - 18 +9

Y = 2X-9

Second,

X + Y = 45

Y = 45 - X

Taking Both the situations,

2X - 9 = 45 - X

3X = 54

X = 54/3 = 18

Y = 45 - 18 = 27

Hence,

Age of Jasmin = 27

Let me know, if needed further assistance.

Hope i helped you.

Thanks for using ' Fixya ' and have a nice day!!

Let the present age of the Rodney = X

present Age of the Jasmin = Y

As per the Situation,

Y-9 = 2 (X - 9)

Y-9 = 2X - 18

Y = 2X - 18 +9

Y = 2X-9

Second,

X + Y = 45

Y = 45 - X

Taking Both the situations,

2X - 9 = 45 - X

3X = 54

X = 54/3 = 18

Y = 45 - 18 = 27

Hence,

Age of Jasmin = 27

Let me know, if needed further assistance.

Hope i helped you.

Thanks for using ' Fixya ' and have a nice day!!

Mar 17, 2010 | Disney Watches

Allan is 19 and Roy is 13.

Solution:

First we have 2 variables, their ages: I used Allan = x & Roy = y

Equation 1: X - 4 = 2*(Y-4) - 3

We can ignore the 5 years in the second part of the statement. Allan will always be 6 years older than Roy whether it be 5 years from now or ten years form now.

Equation 2: X = Y + 6

Substitute Y + 6 for X in equation 1:

X - 4 = 2*(Y-4) - 3 becomes Y + 6 - 4 = 2*(Y-4) - 3

That simplifies to Y + 2 = 2Y - 8 - 3

Rewrite it again: Y + 2 = 2Y - 11

Add 11 to both sides: Y + 13 = 2Y

Subtract Y from both sides: 13 = Y

Now plug 13 in for y in Equation 2

X = Y + 6

X = 13 + 6

X = 19

Solution:

First we have 2 variables, their ages: I used Allan = x & Roy = y

Equation 1: X - 4 = 2*(Y-4) - 3

We can ignore the 5 years in the second part of the statement. Allan will always be 6 years older than Roy whether it be 5 years from now or ten years form now.

Equation 2: X = Y + 6

Substitute Y + 6 for X in equation 1:

X - 4 = 2*(Y-4) - 3 becomes Y + 6 - 4 = 2*(Y-4) - 3

That simplifies to Y + 2 = 2Y - 8 - 3

Rewrite it again: Y + 2 = 2Y - 11

Add 11 to both sides: Y + 13 = 2Y

Subtract Y from both sides: 13 = Y

Now plug 13 in for y in Equation 2

X = Y + 6

X = 13 + 6

X = 19

Oct 08, 2009 | Vivendi Math Blaster Algebra (03763) for...

Paul 3 years younger to his friend peter. In seven years, the product of their ages would be 5 more than the product of their ages 5 years ago. How old are they now?

Oct 31, 2008 | Texas Instruments TI-30XA Calculator

May 23, 2017 | VIA Computers & Internet

228 people viewed this question

Usually answered in minutes!

×